Peran Sutradara dalam Pembuatan Film Dokumenter “Jejak Tradisi Pembuatan Peuyeum Ketan Kabupaten Kuningan” - Rifa Qalbia; Teddy K. Wirakusumah; Aat Ruchiat Nugraha (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2026)
Peuyeum ketan is a fermented sticky-rice product that has long been part of the culture and local economy of Tarikolot Village, Cibeureum District, Kuningan Regency, West Java. This study examines the director’s role in producing the documentary film Jejak Tradisi Pembuatan Peuyeum Ketan Kabupaten Kuningan. The film adopts an expository documentary approach using voice-over narration and features four informants representing the village government, business owner, marketing staff, and consumer. Data were collected through literature review, field observation, and in-depth interviews, then developed through the stages of pre-production, production, and post-production. During pre-production, the director developed the concept, conducted research, selected informants, and prepared production documents. In production, the director supervised cinematography, interviews, and narration. In post-production, the director organized the narrative, supervised editing, and addressed technical challenges. The findings indicate that limited crew members expanded the director’s responsibilities beyond conventional roles, including production planning and direct coordination with informants. The documentary serves as a medium for preserving the Peuyeum ketan tradition while demonstrating its continuing cultural and economic value.